(untitled) (Fiep Bulletin - online, 2015)
The main goal of this research was to analyze the soccer aspirant’s referee’s profile from Mato Grosso do Sul Soccer Federation (FFMS). The results obtained from the physical tests made by the CBF’s referees belonging to FFMS and by the aspirant’s referee were used. (150 meters intermittent running, 40 meters running), fat percentage (equation proposed by Jackson and Pollock), plus the results from a questionnaire for the analysis of the referees profile. This study is descriptive with a cross section, where the subjects were six aspirants referees FFMS that want a vacancy in FFMS, with an age average of 25,8 years old, and 5 referees belonged to CBF, with an age average of 30,6 years old, that act for FFMS and represent the state in the national chart, all of them from the male sex. According to the analysis, it’s possible to observe that there wasn’t any significant difference between the two groups evaluated when compared the fat percentage, the 40 meters shot and the 150 meters intermittent running. Yet, with the analysis of correlation, it was possible to notice that only with the Aspirants Referees FFMS, the fat percentage increased as the evaluated person was older and the time they take to complete the 40 meters running, as the fat percentage increases the capacity of running the 150 meters running decreases, while there was nothing related to their ages with the CBF’s referees. Finally, when it comes about the weekly training frequency, the body fat percentage decreases as the training frequency increases. Besides, the emotional control and psychological with knowing the rules and the development of the cognitive part are important factors for those who choose refereeing as a profession.